2020
DOI: 10.21203/rs.2.21626/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Heat stress induced gut microbiota changes activate TLR4 / NF-κB signaling pathway contributing to inflammatory bowel disease in pigs

Abstract: Background Various stressors alter the 'brain-gut axis' and contribute to many gastrointestinal disorders such as inflammatory bowel disease. However, the pathological mechanisms of these perturbations are poorly understood. Here, we report on the induction of intestinal inflammation in heat-stressed pigs and apply fecal microbiota transplantation from pigs to mice to elucidate the role of intestinal microbiota in TLR4/NF-κB signaling pathway activation. Results Twelve healthy adult pigs were subjected to heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 66 publications
(71 reference statements)
1
3
0
Order By: Relevance
“…Toll-like receptors are a class of classical recognition receptors, such as TLR-2 and TLR-4 , which can recognize the damage-associated molecular patterns to produce several pro-inflammatory cytokines to evoke the host immune response during heat stress [ 15 , 17 ]. In this study, we found that HS up-regulated TLR2/4 mRNA expression meanwhile elevated the expression of pro-inflammatory cytokines TNF-α, IL-6, IL-8 as well as P65 , indicated the activated intestinal immune response under HS, which is consistent with previous report [ 18 ]. Epithelial cells can produce mucins and anti-microbial peptides, which can enhance the intestinal epithelial barrier function by selective microbial permeation and directly influencing microbial populations [ 43 , 44 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Toll-like receptors are a class of classical recognition receptors, such as TLR-2 and TLR-4 , which can recognize the damage-associated molecular patterns to produce several pro-inflammatory cytokines to evoke the host immune response during heat stress [ 15 , 17 ]. In this study, we found that HS up-regulated TLR2/4 mRNA expression meanwhile elevated the expression of pro-inflammatory cytokines TNF-α, IL-6, IL-8 as well as P65 , indicated the activated intestinal immune response under HS, which is consistent with previous report [ 18 ]. Epithelial cells can produce mucins and anti-microbial peptides, which can enhance the intestinal epithelial barrier function by selective microbial permeation and directly influencing microbial populations [ 43 , 44 ].…”
Section: Discussionsupporting
confidence: 93%
“…We found the mucosal immune activation via TLR4/ nuclear factor kappa-B (TLR4/NF-κB) signaling pathway in the ileum by HS. The results of the fecal transplantation experiment also indicated that changes in gut microbial composition promoted by HS could activate the TLR4/NF-κB signaling pathway and cause inflammation in the colon of pigs [ 18 ]. Moreover, stress induces increased permeability of the gut allowing bacteria translocation and mucosal immune activation, which were reported to alter gut microbial composition in turn [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the phylum level, Firmicutes, Bacteroidetes, Proteobacteria , and Spirochetes in ruminal fluid were not changed at different temperatures and humidity levels [ 26 ]. In the same study, the quantification of the bacterial composition using oligonucleotide probes, the relative abundances of the Fibrobacter genus decreased, whereas that of Clostridium coccoides-Eubacterium rectale group, and Streptococcus genus increased due to increasing temperature [ 35 ]. In lactating cows, the relative abundance of fecal Firmicutes was lower and that of fecal Bacteroidetes was higher in the HS (temperature humidity index of 80.5 vs. 66.0) conditions [ 36 ].…”
Section: Microbiota Changes In the Gut By Heat Stressmentioning
confidence: 99%